2005
DOI: 10.1007/bf02712820
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence and metastatic disease in a typical N1 carcinoid bronchial tumour

Abstract: Typical carcinoid bronchial tumour is a well-known disease that, for years, was considered benign. Currently, it is classified within the group of neuro-endocrine lung tumours. It is a low-grade malignancy tumour with a capability of local and distant recurrence. Complete resection with mediastinal lymphadenectomy is the treatment-of-choice. There are, usually, long-term survivors, even in cases of recurrence or mediastinal node invasion. These patients could benefit from removal of recurrent or metastatic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
2
1
0
1
Order By: Relevance
“…Metastatic disease for atypical carcinoid tumors was noted primarily in the bone [26], brain [27], and liver [23], which is consistent with previous reports. We note that for typical carcinoid the most common site of metastasis, when metastasis occurs at all, was the liver and bone, also consistent with previous case reports [26], [28] and [29]. …”
Section: Discussionsupporting
confidence: 92%
“…Metastatic disease for atypical carcinoid tumors was noted primarily in the bone [26], brain [27], and liver [23], which is consistent with previous reports. We note that for typical carcinoid the most common site of metastasis, when metastasis occurs at all, was the liver and bone, also consistent with previous case reports [26], [28] and [29]. …”
Section: Discussionsupporting
confidence: 92%
“…This is contrary to the results reported by Fink et al [21] and Anne Naalsund et al [22] who introduced the right lobe, or Davila DG et al [23] who reported the lower right and left lobes as the most affected sites. Surgery was the most common treatment in our study and lobectomy was performed more than pneumonectomy, which was similar to other studies [24][25][26][27]. Morandi et al [28] reported in 2006 that carcinoid tumors had an equal prevalence between male and female patients and appeared to occur in women at a younger age than men (although this difference was not statistically significant).…”
Section: Discussionsupporting
confidence: 90%
“…Surgery was the most common treatment in our study and lobectomy was performed more than pneumonectomy, which was similar to other studies. [ 25 26 27 28 ] Morandi et al . [ 29 ] reported in 2006 that carcinoid tumors had an equal prevalence of gender and appeared to occur in women at a younger age than men (although this difference was not statistically significant).…”
Section: Discussionmentioning
confidence: 99%